Analisis Dampak Perubahan Arus Pengelasan Terhadap Kekuatan Sambungan Las Pada Material Stainless Steel 316 - Salim, Victor; Rosehan, Rosehan; Lubis, Sobron Yamin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
In a situation of increasing urbanization in the capital, the demand for decent and quality housing is also increasing rapidly. This increase was in line with increasing market demand for specific construction products such as railings, doors and windows which are of good quality. The research method and data collection will start from nine pairs of 316 stainless steel plates which will be welded using SMAW welding. Welding on stainless steel plates will be carried out with varying welding currents of 60 A, 70 A and 80 A. Each of these welding currents will be carried out on three stainless steel plates. The results showed that the use of a higher variation of welding current in the welding process resulted in a higher strength of the welded joint. The elastic modulus can decrease due to several factors such as the presence of microscopic cracks, changes in crystal structure, or changes in the bonds between atoms or molecules of the material. The strength of welded joints in stainless steel 316 material can also be affected by other factors besides variations in welding current. Parameters such as mains voltage, welding time and type of electrode also contribute to the strength of the welded joint.